A scoping review of the application of motor learning principles to optimize myoelectric prosthetic hand control. Issue 3 (17th June 2022) - Parr, Johnny V. V.; Wright, David J.; Uiga, Liis; Marshall, Ben; Mohamed, Mohamed Omar; Wood, Greg
Abstract : Although prosthetic hand rejection rates remain high, evidence suggests that effective training plays a major role in device acceptance. Receiving training early in the rehabilitation process also enhances functional prosthetic use, decreases the likelihood of developing an overreliance on the intact limb, and reduces amputation-related pain. Despite these obvious benefits, there is a current lack of evidence regarding the most effective training techniques to facilitate myoelectric prosthetic hand control, and it remains unknown whether training is effective in facilitating the acquisition and transfer of prosthetic skill. In this scoping review, we introduced and summarized key motor learning principles related to attentional focus, implicit motor learning, training eye–hand coordination, practice variability, motor imagery, and action observation, and virtual training and biofeedback. We then reviewed the existing literature that has applied these principles for training prosthetic hand control before outlining future avenues for further research. The importance of optimizing early and appropriate training cannot be overlooked. While the intuition and experience of clinicians holds enormous value, evidence-based guidelines based on well-established motor learning principles will also be crucial for training effective prosthetic hand control. While it is clear that more research is needed to form the basis of such guidelines, it is hoped that this review highlights the potential avenues for this work.